The contribution of language contact to the emergence of World Englishes - Lim, Lisa (Cambridge University Press, 2020)
A contemplation of the emergence of World Englishes is essentially a contemplation of the phenomenon of contact between communities and languages. This chapter outlines the evolution of Englishes outside the British Isles, with particular attention to non-settler, exploitation colonies, in many ways viewed as the epitome of language contact dynamics. It takes into account not only contact between the English-speaking and indigenous language communities during Britain’s trade and colonisation ventures from the 17th through 19th centuries, but also highlights other circumstances pre-dating British colonisation often overlooked in the field, comprising a larger group of players, in a chain of contact, such as that amongst various Asian communities, and with the Portuguese. Features such as tone, particles, and mixed codes are discussed: although traditionally regarded as the outcome of imperfect learning, such restructuring illustrates how, with diverse ecologies and typologies, there are no constraints on the typology of the emergent World English varieties. Also underscored is the fact that the dynamics and outcomes of contact in World Englishes are not distinct from those observed in other contact scenarios in which creole languages evolve. This chapter concludes by evaluating the current and future evolution of English as a result of contemporary contact ecologies, including computer-mediated communication, the language teaching industry, and trade.